Spinal Cord Schistosomiasis - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1991)
A seven year old girl with Schistosoma mansoni infection of the spinal cord mimicking cord neoplasm is reported from the Department of Neurology, University of Michigan, Ann Arbor, MI.